2018
DOI: 10.1016/j.cirp.2018.04.047
|View full text |Cite
|
Sign up to set email alerts
|

A geometrical model for managing surface productivity of U-shaped assembly lines

Abstract: Portal del coneixement obert de la UPC http://upcommons.upc.edu/e-prints Aquesta és una còpia de la versió author's final draft d'un article publicat a la revista CIRP annals. Manufacturing Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A review and categorization of in-plant milk runs reported that material handling occupies 55% of a factory's surface [14]. Recent research on milk-run design, such as the Vehicle Routing Problem (VRP), has focused mainly on minimizing the total distance travelled or minimizing the number of vehicles applied [15,16] but less attention has been paid to milk-run design for surface reduction and handling productivity [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A review and categorization of in-plant milk runs reported that material handling occupies 55% of a factory's surface [14]. Recent research on milk-run design, such as the Vehicle Routing Problem (VRP), has focused mainly on minimizing the total distance travelled or minimizing the number of vehicles applied [15,16] but less attention has been paid to milk-run design for surface reduction and handling productivity [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reduce P as much as possible. This is particularly relevant because, accordingly to [17], production cells surface has a quadratic relationship with P. Nevertheless, P reduction has some limits: the shorter the P, the more trips from storage to POUs are needed, so more driving time is added to mizusumashi workload.…”
Section: Surface Reduction Factorsmentioning
confidence: 99%
See 1 more Smart Citation